The Development of 2D Animation Video for Visitors at UTHM - Hamid, Hashima; Subramaniam, Teevea (Research and Innovation in Technical and Vocational Education and Training, 2025)
```Visitor guidelines are crucial for maintaining safety, order, and a positive experience for both visitors and those being visited in various settings, including hospitals, correctional facilities, tourist destinations and educational institutions like UTHM. Visitor guidelines are often communicated through signs, brochures, or online resources, providing visitors with clear instructions and expectations. Hence, this study is about the development of the 2D Animation Video for Visitors at UTHM to help them to explore the UTHM area easily. At the same time, this 2D animated video development serves as a medium to convey significant information related to the location and buildings that exist within the UTHM in detail. With the development of this 2D animated video, visitors can explore UTHM buildings, building information, and building locations. Visitors from a variety of ethnic groups, age backgrounds, and different levels of learning ability can recognize and understand building layout and information about building placement through visual exposure. The Waterfall Model is used as a study methodology to guide the entire process of developing this 2D animated video. Meanwhile, the testing and evaluation of this 2D animated video were carried out using a survey instrument, with four experts selected to conduct the functionality testing and design of this 2D animated video. Through the results of the studies carried out, all experts have given comments and suggestions for positive improvements to the 2D animated video that has been developed. Overall, these 2D animated videos can serve as additional information for visitors that can maintain their motivation of visitors to explore UTHM.